New possibilities for machined surface quality improvements - Vasilko, Karol (Communications - Scientific Letters of the University of Zilina, 1999)
The main relationships governing the machining processinclude the relationship between the roughness of the machined surface, the feed and the curvature radius of the tool tip expressed by the approximate equation: Ry f2/8r ε . According to this equation, an increase of the feed increases the capacity of the surface roughness, according to aparabolic law. This fact prevents large increases in the productivity of machining. There are certain reserves in increasing the curvature radius of the tip which is present in the denominator. However, very large increase of the tip diameter increases the length of the cutting edge in engagement and causes vibration of the system. It is therefore necessary to find other solutions. One of them is the so-called Kolesov tool, with a section of the secondary cutting edge with setting angle of 00. In contrast to these solution, the author proposes an original concept, together with its partial verification.
Keywords: no keywords